Deixis And Maxim In EFL Classroom Videos - Fitri Ningsi; Ramli; Reynaldi Saputra (JURNAL PENDIDIKAN BAHASA, 2020)
The aim of this research is to investigate the use of deixis by teachers and the floating of maxim in EFL classroom videos. It is hopefully will be useful for the institution where the researcher studies, for other students, other researchers, or readers in general. This research uses descriptive qualitative method. There are four videos which were used as source of data. In collecting the data, the researcher transcribes the videos, classify the data based on types of deixis and maxim. After all of the data were collected, the researcher analyze the data and draw the conclusion. The result of this research can be seen as follows: (1) There are found 996 deixis used by teachers in EFL classroom videos, which consist of 617 person deixis, 217 discourse deisis, 124 temporal deixis, 24 spatial deixis, and 14 social deixis. (2) There are found 119 maxims floated in the videos, which consist of 68 maxim of quantity floated, 28 maxim of relation floated, 14 maxim of quality floated, and 9 maxim of manner floated. Those results show that the most dominant type of deixis used is Person Deixis, and the most dominant type of maxim floated is Maxim of Quantity.